2016
DOI: 10.3389/fnins.2016.00390
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Expression of Metabolic, Structural, and Immune Pathways in Early Myopia and Hyperopia

Abstract: Myopia (short-sightedness) affects 1.45 billion people worldwide, many of whom will develop sight-threatening secondary disorders. Myopic eyes are characterized by excessive size while hyperopic (long-sighted) eyes are typically small. The biological and genetic mechanisms underpinning the retina's local control of these growth patterns remain unclear. In the present study, we used RNA sequencing to examine gene expression in the retina/RPE/choroid across 3 days of optically-induced myopia and hyperopia induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 84 publications
(125 reference statements)
13
58
0
Order By: Relevance
“…This review will concentrate on myopia (i.e., nearsightedness) because its prevalence is high, it is associated with significant ocular complications, and most recent research addresses mechanisms for myopia development as distinct from hyperopia (i.e., farsightedness). Importantly, considerable literature suggests that the mechanisms responsible for myopia vs hyperopia are not just reciprocal, but may be different …”
Section: Introductionmentioning
confidence: 99%
“…This review will concentrate on myopia (i.e., nearsightedness) because its prevalence is high, it is associated with significant ocular complications, and most recent research addresses mechanisms for myopia development as distinct from hyperopia (i.e., farsightedness). Importantly, considerable literature suggests that the mechanisms responsible for myopia vs hyperopia are not just reciprocal, but may be different …”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Concurrently, the role of visual experience in adapting ocular growth to suit the environment has been extensively investigated in animals where myopia can be induced by rearing with form deprivation occluders or negatively powered defocusing lenses. 19 Transcriptome and proteomics studies of ocular expression profiles in these animal models have associated thousands of genes [20][21][22][23][24][25][26][27][28] and hundreds of proteins [29][30][31][32][33][34][35][36][37] with environmentally driven growth. Enrichment analyses have aided interpretation of the wealth of data generated by exploratory human and animal studies 20,38 ; however, the key pathways by which genes and environment control ocular growth remain largely unclear.…”
mentioning
confidence: 99%
“…These loci implicate genes involved in multiple cellular and biological processes related to extracellular matrix organization, eye morphogenesis, retinal signaling, and visual perception [53,54]. Gene expression profiling studies also showed that development of myopia is accompanied by changes in gene expression in the retina, choroid, and sclera [39,[55][56][57][58][59][60][61][62].…”
Section: One Of the Leading Causes Of Vision Loss In Several Parts Ofmentioning
confidence: 99%